Brachytherapy for oligometastatic prostate cancer to the penis - Martz, Nicolas; Benziane-Ouaritini, Nicolas; Gautier, Mathieu; Brenot-Rossi, Isabelle; Montagne, Lucile; Salem, Naji; Bodokh, Yohan; Hannoun-Levi, Jean-Michel (Journal of Contemporary Brachytherapy, 2021)
The origin of penile metastases is in 70% of cases from primary pelvic cancers (genitourinary and recto-sigmoid primary tumors). The prognosis is poor and it is often associated with synchronous bone metastases at the time of diagnosis. We present the case of a 61-year-old patient who developed a penile induration 7 years after radical prostatectomy followed by adjuvant external beam radiation therapy for high-risk prostatic adenocarcinoma. Biopsies confirmed the metastatic localization and a detailed assessment failed to find any further remote lesions. Faced with this penile oligometastatic prostate cancer, we proposed an ablative treatment based on interstitial multi-catheter high-dose rate brachytherapy. At the six-month follow-up, clinical examination and 68Ga-PSMA-11-PET confirmed a complete response of the penile tumor without new lesion at a distance.